2017
DOI: 10.1038/ncomms15089
|View full text |Cite
|
Sign up to set email alerts
|

A mouse tissue transcription factor atlas

Abstract: Transcription factors (TFs) drive various biological processes ranging from embryonic development to carcinogenesis. Here, we employ a recently developed concatenated tandem array of consensus TF response elements (catTFRE) approach to profile the activated TFs in 24 adult and 8 fetal mouse tissues on proteome scale. A total of 941 TFs are quantitatively identified, representing over 60% of the TFs in the mouse genome. Using an integrated omics approach, we present a TF network in the major organs of the mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 64 publications
3
95
0
Order By: Relevance
“…To investigate the biological roles of the tissue-specific versus the globally expressed proteins, we performed a gene ontology (GO) enrichment analysis across the proteinspecific tissue distributions, and found that globally expressed proteins are enriched for mitochondrial proteins involved in oxidative phosphorylation, whereas transcription factors 27 are generally tissue-specific proteins ( Figure 5J). These findings are consistent with the fact that cellular housekeeping functions such as ATP production by oxidative phosphorylation is generic to all cell types, whereas tissue specificity is facilitated by temporal and spatial gene expression patterns, which are driven by transcription factors 28 .…”
Section: Quantitative Rat Organ Protein Atlas By Tmt and Dia-lfqsupporting
confidence: 86%
“…To investigate the biological roles of the tissue-specific versus the globally expressed proteins, we performed a gene ontology (GO) enrichment analysis across the proteinspecific tissue distributions, and found that globally expressed proteins are enriched for mitochondrial proteins involved in oxidative phosphorylation, whereas transcription factors 27 are generally tissue-specific proteins ( Figure 5J). These findings are consistent with the fact that cellular housekeeping functions such as ATP production by oxidative phosphorylation is generic to all cell types, whereas tissue specificity is facilitated by temporal and spatial gene expression patterns, which are driven by transcription factors 28 .…”
Section: Quantitative Rat Organ Protein Atlas By Tmt and Dia-lfqsupporting
confidence: 86%
“…Although several miRNAs share the promoter of the host gene for their transcription, many might have separate promoters in the intronic region and may be transcribed independently of the host gene (24). Because ALR does not appear to have transcriptional activity (28), it may not directly influence the miRNA expression despite its presence in the nucleus. However, it is likely that ALR may associate with transcription factors and act as a coactivator or -repressor.…”
Section: Discussionmentioning
confidence: 99%
“…Although present in the nucleus, ALR does not seem to possess DNA-binding sequence (28), and thus unlikely to directly modulate gene expression including that of miRNAs. Because ALR depletion increases oxidative stress both in vivo and in vitro (5), ALR flox/flox hepatocytes were exposed to oxidative stress by H 2 O 2 or transfected with Adeno-Cre (Cell Biolabs).…”
Section: Alr Depletion From Hepatocytes Reduces Ppara Acox1 and Pmp70mentioning
confidence: 99%
“…In the mammalian genome, there are approximately 1500 transcription factors (TFs) (Zhou et al 2017;Vaquerizas et al 2009), which bind to specific DNA sequences, within cis-regulatory modules (CRMs), to control gene expression and regulate almost every aspect of life. Many are used repeatedly, and in a variety of combinations, to regulate distinct developmental and homeostatic events.…”
Section: Introductionmentioning
confidence: 99%